Digital clock with azan reader / Hanisah Mohamed Nadzar and Siti Farah Ahmad Fadzir - Mohamed Nadzar, Hanisah; Ahmad Fadzir, Siti Farah (2005)
The advancement of technology has given many benefits to human being and universe as a whole. We can see obviously the changes in the engineering and medical field. The evolution of electrical engineering knowledge has give create many changes to the world. The creation of transistor in the middle of 20th century by three scientists has a very big impact to the revolution of computer, communications, and digital. One of the technologies of digital, this project that use the digital system is converted. Digital azan clock is similarly like the alarm clock but is produced an azan when the set of time is triggered. Besides, it must set on five different times to produce an azan on five times that are Subuh, Zuhor, Asar, Maghrib, and Isha’. Then using software sets the time of prayer